فتاوی نوریہ کے منہج و اسلوب اور عصری مسائل کا تحقیقی جائزہ: A Research study on the Methodology of Fatawa Nooria - Rasool, Farhat; Ullah, Dr. Muhammad Zia (Al-Irfan, 2024)
Fatawa Nooriya, authored by Fqih-e-Azam Allama Noor Ullah Naeemi, serves as a seminal work in Islamic jurisprudence, known for its comprehensive analysis and scholarly insights. This abstract explores the distinctive manhaj (methodology) and stylistic approach employed by Naeemi in Fatawi Nooriya. Naeemi adopts a meticulous methodology grounded in classical Islamic scholarship, drawing upon primary sources such as the Quran, Sunnah, and classical juristic texts. He emphasizes the principles of ijtihad (independent reasoning) within the framework of established legal doctrines, offering nuanced interpretations tailored to contemporary contexts. Naeemi’s style reflects a blend of traditional scholarship and modern relevance, characterized by clarity, logical coherence, and a commitment to upholding the principles of Islamic jurisprudence. Through Fatawi Nooriya, Naeemi contributes to the ongoing discourse on Islamic law, providing valuable insights into the application of Sharia principles in contemporary society.